Increased delayed reward during intertemporal decision-making in schizophrenic patients and their unaffected siblings. (April 2018) - Wang, Lu; Jin, Shengchun; He, Kongliang; Chen, Xingui; Ji, Gongjun; Bai, Xiaomeng; Xiao, Guixian; Ma, Huijuan; Wang, Kai
Abstract: Intertemporal choices are decisions with consequences in multiple time periods and constitute a significant part of social cognition. The shared neuropathological characteristics of patients with schizophrenia and their siblings might express intermediate phenotypes in behavior that could be used to further characterize the illness. Schizophrenic patients, unaffected siblings, and healthy controls underwent a computerized version of the "Intertemporal Choice Task". All participants could choose between sooner-smaller (SS) and later-larger (LL) options in now-trials and in not-now-trials. Subjects also underwent a battery of cognitive neuropsychological assessment. Our results indicated that schizophrenic patients and unaffected siblings both had a tendency to choose LL options in now-trials or not-now-trials compared to healthy controls. Schizophrenic patients had significantly lower scores in several cognitive tasks, including MoCA, attention, executive functions, and information processing when compared with the other two groups. Moreover, within the schizophrenic patient group, significant correlations were found between intertemporal decision-making performance and executive function. The present study showed that both schizophrenic patients and unaffected siblings preferred to choose larger-delayed rewards during intertemporal decision-making, which may result from frontal-striatal and frontal-parietal network dysfunction. Their intertemporal decision-making performance was associated with executive function performance. Highlights: Siblings of schizophrenic patients have a higher risk of developing the disorder compared to the general population. Schizophrenic patients and unaffected siblings both had a tendency to choose later-larger options during intertemporal decision-making. The preference of schizophrenia and siblings in intertemporal choice potentially may result from frontal-striatal and frontal-parietal network dysfunction. Intertemporal decision-making performance may be associated with executive function performance.